Trap‐dependence in capture–recapture studies: empirical evidence in vertebrates and biological meaning - Cachelou, Jessica; Gaillard, Jean‐Michel; Chassagneux, Agathe; Baubet, Eric; Gamelon, Marlène (Oikos, 2025)
Capture–recapture (CR) models have been used for decades to estimate population size and demographic rates in natural populations from the monitoring of individuals. One of the most frequent deviations from assumptions required in CR studies is the immediate trap‐dependence that corresponds to the correlation between capture events. We review empirical evidence of immediate trap‐dependence across vertebrate populations where several capture types exist, record possible variation in the occurrence and the sign of trap‐dependence and discuss its biological meaning. We highlight that when trap‐dependence occurs, trap‐happiness, the higher probability for an individual to be captured again at i + 1 if captured at i , is the rule rather than the exception, whatever the type of capture. However, the occurrence of trap‐dependence varies among populations of a given species and only displays a moderate repeatability in a given species. It also varies within a population depending on sex, age, or type of mark, and reflects among‐individual variation in personality (bold versus shy), social status, or ecological context. We argue that immediate trap‐dependence can be seen as a form of dynamic heterogeneity, reflecting clear among‐individual differences. Although trap‐dependence is generally considered simply as a noise to account for, it has a clear biological meaning in terms of among‐individual differences.